Economic threshold as a criterion for management decision of concurrent rice genotypes in flooded rice - Agostinetto, Dirceu; Fleck, Nilson Gilberto; Rizzardi, Mauro Antonio; Junior, Alvadi Antonio Balbinot (Pesquisa Agropecuaria Brasileira, 2005)
The economic thresholds (ET) for weedy rice infestations in rice fields allow to decide the management of the rice crop, rationalizing herbicide use. The aim of this research was to estimate ET for red rice and for EEA 406 rice cultivar, mimicking red rice, when competing with flooded rice. Three field experiments were carried out, during the 1999/2000 and 2000/2001 growing seasons. The investigated factors were populations of the concurrents genotypes on the three experiments and red rice relative emergence times (first study), EEA 406 rice cultivar (second study) and rice cultivars and row widths (third experiment). ET values for red rice were lower than those for EEA 406 genotype. The ET values estimated for EEA 406 varied widely, according to environment (seasons), emergence time, rice cultivar and row width variables. Earlier emergence of concurrent genotypes in relation to the crop, increase in row width, and use of very early maturity cultivars decreased the ET values. Increases in grain yield, selling rice price and in control efficiency, and control cost reduction, decreased ET levels, making cost effective the adoption of management practices under lower concurrent genotype populations.